2017
DOI: 10.1038/s41598-017-08162-z
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of a Streptococcus dysgalactiae subspecies equisimilis stG62647-lineage associated with severe clinical manifestations

Abstract: Increasing incidence rates of invasive Streptococcus dysgalactiae subspecies equisimilis (SDSE) infections have been reported worldwide, but the evolutionary mechanisms underlying this development remain elusive. Through prospective surveillance of invasive SDSE infections in western Norway, we observed the emergence of a novel and virulent SDSE genotype, stG62647. This emm-type, rarely encountered as a cause of invasive disease during 1999–2012, emerged in 2013 as the predominant SDSE-genotype. The stG62647-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 43 publications
5
33
0
Order By: Relevance
“…Even though several other emm types where identified, the fact that >70% of the isolates belonged to only 3 emm types add to the evidence that some emm types have a particular ability to cause severe infections [ 11 , 28 , 29 ]. In SD, stG62747 was the predominant emm type, in accordance with a previous report from our region [ 30 ]. The virulence gene profiles of GAS largely reflected the emm type distribution, with a high proportion with speA and speG consistent with the predominance of emm1 and emm3 types.…”
Section: Discussionsupporting
confidence: 92%
“…Even though several other emm types where identified, the fact that >70% of the isolates belonged to only 3 emm types add to the evidence that some emm types have a particular ability to cause severe infections [ 11 , 28 , 29 ]. In SD, stG62747 was the predominant emm type, in accordance with a previous report from our region [ 30 ]. The virulence gene profiles of GAS largely reflected the emm type distribution, with a high proportion with speA and speG consistent with the predominance of emm1 and emm3 types.…”
Section: Discussionsupporting
confidence: 92%
“…Similar conclusions have been drawn in studies on tissue tropism in Staphylococcus aureus [ 24 ]. Our findings are further corroborated by the diverse clinical manifestations produced by virtually identical isolates in clonal outbreaks of S. pyogenes and SDSE disease [ 25 , 26 ]. However, exploring bacterial pathogens only at the DNA-level, precludes the consideration of transcriptional and translational regulatory events, and further studies are warranted to encompass these aspects.…”
Section: Discussionsupporting
confidence: 72%
“…The assemblies were assessed using Quast [ 35 ], and RAST was used for annotation [ 36 ]. emm -type and MLST-profiles were identified as previously outlined [ 26 ], and novel MLST alleles and profiles were submitted to pubMLST ( www.pubMLST.org ). SNP based phylogenetic analysis was performed [ 37 ], using Streptococcus dysgalactiae subspecies equisimilis ATCC 12394 (GenBank accession number CP002215) as a reference-genome.…”
Section: Methodsmentioning
confidence: 99%
“…The increased expression of coding genes was observed in strong biofilm-producing strains ( Genteluci et al, 2015 ). Oppegaard et al (2017) showed that genetic alterations in the pilus-region (also known as the FCT-region – Fibronectin and Collagen binding, and T-antigen) were associated with bacteria’s propensity to adhere to different surfaces, which could also be related to the expression of a wide range of adhesins putatively encoded in this region, including proteins predicted to adhere to collagen and fibronectin. Interestingly, although they are genomic closely related, the presence of fibrillary-like structures was not observed in SDSD strains.…”
Section: Biofilms Formation and Dispersalmentioning
confidence: 99%